Pharmacokinetics of Oral Cholecalciferol in Healthy Subjects with Vitamin D Deficiency: A Randomized Open-Label Study - Fassio, Angelo (Nutrients, 2020)
Background: The aim of this study was to investigate the pharmacokinetic (PK) and safety profile of high-dose vitamin D supplementation, comparing different schedules (daily, weekly, or bi-weekly) in an otherwise healthy vitamin D-deficient population. Methods: Single-center, open-label study on healthy subjects deficient in vitamin D (25 (OH)D < 20 ng/mL), randomized to receive cholecalciferol (DIBASE(®), Abiogen Pharma, Italy) using three different schedules: Group A: 10,000 IU/day for eight weeks followed by 1000 IU/day for four weeks; Group B: 50,000 IU/week for 12 weeks, Group C: 100,000 IU/every other week for 12 weeks. Total cumulative doses were: 588,000 IU, 600,000 IU, 600,000 IU. The treatment regimens corresponded to the highest doses allowed for cholecalciferol for the correction of vitamin D deficiency in adults in Italy. Results: mean 25 (OH)D plasma levels significantly increased from baseline 13.5 ± 3.7 ng/mL to peak values of 81.0 ± 15.0 ng/mL in Group A, 63.6 ± 7.9 ng/mL in Group B and 59.4 ± 12 ng/mL in Group C. On day 28, all subjects showed 25 (OH)D levels ≥20 ng/mL and 93.1% had 25 (OH)D levels ≥30 ng/mL. On day 56 and 84, all subjects had 25 (OH)D levels ≥30 ng/mL. No serious adverse events occurred during the study. Conclusions: normalization of 25 (OH)D serum levels was quickly attained with all the studied regimens. A more refracted schedule provided a higher systemic 25 (OH)D exposure.